Evaluation of the Gastrointestinal Parasite Burden of Goats in Traditional Breeding in Benin - Challaton1, Kétomon Pierre; AKOUEDEGNI, COOVI GUENOLE (My University, 2023)
Goat farming in Benin is traditional. In this system, animals harbor parasites that cause economic losses related to growth and reproduction performance, which strongly affect farm productivity. The objective of this study was to evaluate the gastrointestinal parasite burden of goats in Benin. Thus, feces were sampled from 572 and 497 goats in the rainy and dry seasons, respectively, in southern, central and northern Benin. The parasite inventory was performed using the Mini-FLOTAC technique for the quantitative study and the Baermann method for the qualitative research. The results showed an overall prevalence of gastrointestinal parasites of 96.82 %. Furthermore, goats were mainly infected with coccidia (92.24 %); strongyles (83.91 %), of which the critical genera were Haemonchus sp., Trichostrongylus sp., and Oesophagostomum spp. ; Strongyloides spp. (73.25 %) followed by Moniezia spp. (21.8 %). Other gastrointestinal parasites retrieved were Trichuris sp. (0.94%) and Toxocara sp. (0.28%). Infestation rates and the number of Eggs Per Gram of feces (EPG) or Oocysts Per Gram of feces (OPG) were higher in the wet season than in the dry season. During the wet season, infestations were severe for strongyles, Moniezia spp., coccidian, and moderate for Strongyloides spp. and light during the dry season except for coccidia, where they were intense. Infestation rates and egg excretion of gastrointestinal parasites were shaped by age, sex, breed, and study areas. This knowledge of gastrointestinal parasites will help guide for the surveillance of goat parasitosis in Benin.
Keywords: Benin; Breeding; Gastrointestinal parasites; Strongyles; Goats